Autoimmunity-Related Granulomatous Dermatitis in Association with Hepatitis - Grégory Szepetiuk; Marianne Lesuisse; Gérald E. Piérard; Pascale Quatresooz; Claudine Piérard-Franchimont (Karger Publishers, 2012)
Aim: Both interstitial granulomatous dermatitis (IGD) and palisaded neutrophilic granulomatous dermatitis (PNGD) are rare disorders typically associated with systemic autoimmune conditions. They probably represent different aspects of a disease spectrum encompassing the concept of autoimmunity-related granulomatous dermatitis (ARGD). Case Report: A 61-year-old woman presented with ARGD and autoimmune hepatitis. The clinical presentation suggested PNGD, while histopathology was consistent with IGD. Discussion: The association of ARGD with autoimmune hepatitis is apparently a rare event. The present case shows that the clinicopathological correlation in ARGD does not always clearly fit with the classical presentations of IGD or PNGD.